Methods for valorization of mining companies: the analysis for the peruvian case 2008 - 2013 - Bustamante, Rafael (2014)
In this research the different financial literature on methods of valuation of companies is explained. In a second term by using the same, which holds that it isthe valuation by the method of free cash flow discounted at a discount rate called: Weighted Average Cost of Capital, the most complete method. The valorization for two major mining companies in the Peruvian economy is obtained: Southern Copper Corporation (SCC) and Volcan Cia Minera (VOLCAN).